INTEGRATION OF DIDACTIC AUDIO DESCRIPTION INTO THE SCHOOL CURRICULUM - Costa, Denise Ferreira; Azevedo, Fernanda Monteles de Oliveira; Rosa, Nascimento da Silveira; de Faria, Maria Soraia Nascimento Corrêa (Seven Editora, 2026)
This article aims to discuss the integration of didactic audio description into the school curriculum, justifying the need for its inclusion in the educational context. The objective is to identify the challenges and difficulties that emerge from pedagogical practices during the implementation process of this strategy. This is a bibliographic research, which is based on the academic production developed in the country, especially in the works of Motta (2010) and Mianes (2023), as well as in the current legislation that regulates and guides the use of audio description as a tool for accessibility and inclusion of public students of special education. It is noteworthy that advances have been recorded in Brazil regarding the use of audio description in the school environment, promoting inclusion and equity in learning. However, it is important to highlight that there are still many challenges to be overcome, especially with regard to the initial and continuing training of teachers, in order to promote understanding about the possibilities of curricular flexibility, focusing on pedagogical practices that address the learning diversity of students.